Design and Development of a Microscopic Electrical Impedance Tomography System - Fazalul Rahiman, Mohd Hafiz (International Journal of Integrated Engineering, 2017)
Basically, Electrical impedance tomography is a new technique in monitoring and imaging cross sectional images and physical state of objects by measuring the internal impedance distribution. This paper presents the design of a microscopic electrical impedance tomography system, which is a non-destructive approach that has the capability to interpret and analyze the internal impedance distribution of a medium (the system) and reconstruct its image as a tomogram, where any object inside the system can be shown in a 2D (two-dimension) image. A current source circuit was constructed and studied by injecting 5 mA of current to an array of electrodes (3*3 array). Moreover, the conditional measurement circuit is going to receive voltage from measurement electrodes array of 8*16 in each plane.Â  The data was obtained from both planes as a matrix of 8*16 electrodes using multiplexers which was transferred serially to the PC to be analyzed and to reconstruct the image/tomogram. The image reconstruction process and algorithms were engaged in the calculation to reconstruct the image based on the voltage collected. Finally, interpolation is conducted to improve the quality and increase the resolution of the image.